2020
DOI: 10.1039/d0bm00964d
|View full text |Cite
|
Sign up to set email alerts
|

Exploring microfluidics as a tool to evaluate the biological properties of a titanium alloy under dynamic conditions

Abstract: To bring novel biomaterials to clinical use, reliable in vitro models are imperative. The aim of this work was to develop a microfluidic tool to evaluate the biological properties of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…2 The protein and cellular adsorption behavior displayed in new and emergent approaches that may better reproduce the physiologic dynamic environment would be interesting to examine in the future. 29,39,40 Overall, this study proves the importance that the preincubation step in a serum-supplemented medium may have on biomaterials, whereby it enhances early cellular adhesion responses. Moreover, it was shown that computational modeling, in this case through the usage of two Langmuir isotherm equations that allowed coupling of protein-cell adhesion, enabled an accurate prediction of cell adhesion behavior over time.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…2 The protein and cellular adsorption behavior displayed in new and emergent approaches that may better reproduce the physiologic dynamic environment would be interesting to examine in the future. 29,39,40 Overall, this study proves the importance that the preincubation step in a serum-supplemented medium may have on biomaterials, whereby it enhances early cellular adhesion responses. Moreover, it was shown that computational modeling, in this case through the usage of two Langmuir isotherm equations that allowed coupling of protein-cell adhesion, enabled an accurate prediction of cell adhesion behavior over time.…”
Section: Discussionsupporting
confidence: 54%
“…In the current work, the cells were cultured under static conditions in standard well plates, although the environment created is known to poorly mimic the real physiological conditions . The protein and cellular adsorption behavior displayed in new and emergent approaches that may better reproduce the physiologic dynamic environment would be interesting to examine in the future. ,, …”
Section: Discussionmentioning
confidence: 99%
“…OoC platforms can be used to study the biocompatibility and efficacy of biomaterials in an environ ment that is representative of the (patho)physiology of the organ or tissue to be replaced, repaired or regenerated. An important consideration is the integration of various biomaterials into the microfluidic OoC systems for fast and parallelized biocompatibility or biofunctionality testing 154,155 . Numerous different solutions for facile and versatile integration of biomaterials of various geometries 156,157 or bonding strategies have been reported 158 .…”
Section: Biomaterials Testingmentioning
confidence: 99%
“…Taken together, these results demonstrate that hBCSFB-on-chip recreates some physiologically-relevant functions, which are also in line with previous studies showing that dynamic flow can improve the biological properties of cells. 34,37…”
Section: Hbcsfb-on-chip Recapitulates the Physiologically-relevant Tr...mentioning
confidence: 99%